The Practice of Discretion in Implementing Forest-Rehabilitation Policy in Forest Management Unit - Adi Dzikrullah Bahri (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
This study analyzed the implementation of discretion in forest and land rehabilitation policy (RHL) on street-level bureaucracy (SLB). The study conducted at Forest Management Unit (KPHL) Rinjani Barat, used Michael Lipsky's conception about street-level bureaucracy and discretion in the forest management. The result shows the history and forest tenure problem become a forest management framework for SLB. Because of that, forest management from top down system has changed to participatory between SLB and communities. The result of RHL policy is sucess story, good forest management and community welfare.